Negotiating, Communicating, Collaborating: A Sociocultural View of Online Program Development - Frizelle, Sara Jane (My University, 2016)
Online learning has brought about changes to nearly every sphere of the university from the definition of the student, to the curriculum, to the way we know and understand teaching and learning, to policies that govern our institutions. Because online learning is such a departure from the traditional 4-year university experience and from traditional ways of teaching and learning, it has continually struggled to be seen as a legitimate way to approach educating students. This is evidenced by how college and university leaders have approached the policies and practices that have surrounded online learning. As online, hybrid, and web-enhanced instruction become more pervasive in higher education, college and university administrators are challenged with the task of strategically creating online courses and programs. This qualitative case study attempted to close that gap by using a sociocultural methodology to examine how institutional leaders of a newly formed online program negotiate both main and branch campus policies and more specifically, by studying the consequences this negotiation had for online program development. Data collection strategies included semi-structured interviews with program faculty and administrators, observation of departmental meetings, and document review of campus policies, faculty handbooks, meeting notes and the university website. This research has contributed to the literature by examining online program development from a sociocultural perspective that values the cultural and historical aspects of policy.
Thesis (Ph.D.)--University of Washington, 2016-05
Keywords: Cultural Historical Activity Theory (CHAT); Distance Education; eLearning; Higher Education; Online Learning; Relational Agency; Educational technology; Education policy; Educational leadership; education - seattle